Antioxidant Effect of GOYO-11 Against Aspirin-Induced Gastric Ulcer in Rats - Gaowa, Suolong; Ponkhoon, Kherlen; Ankhbayar, Bayartsetseg; Namdag, Bira; Dalkh, Tserendagva (Central Asian Journal of Medical Sciences, 2021)
Objectives: This study aimed to investigate the protective effects of GOYO-11 on aspirin-induced gastric ulcer formation. Methods: The prevention of aspirin-induced gastric ulcers was studied in 60 rats divided into 6 equally sized groups: healthy group (no aspirin), control group (aspirin-only), standard drug group (aspirin + omeprazole and bismuth), GOYO-11 (aspirin + GOYO-11 50 mg/kg, 100 mg/kg, 150 mg/kg, respectively). Results: The aspirin-only control group had distinctly attenuated activities of superoxide dismutase, catalase, glutathione peroxidase compared to the healthy group (p < 0.05). The control group showed a significant elevation in malondialdehyde levels compared to the healthy group (p < 0.05). The GOYO-11 high dose group had a significant elevation in superoxide dismutase levels compared to the control group (p < 0.05). The GOYO-11 middle dose group showed significant elevation in catalase, superoxide dismutase, glutathione peroxidase levels compared to the control group with a significant reduction in malondialdehyde level when compared to the control group (p < 0.05). Conclusions: GOYO-11 had a gastroprotective effect against aspirin-induced gastric ulcer rats and probably prevents ulcers by protecting the antioxidants, inhibiting lipid peroxidation (malondialdehyde), saving mucous glycoprotein, and decreasing the infiltration of inflammatory cells.